Peculiarities of the development, course and diagnostic principles of food anaphylaxis in toddlers - L.V. Besh (Zdorovʹe Rebenka, 2021)
Food anaphylaxis at an early age can be characterized by a development of nonspecific symptoms, including a child’s persistent crying, drowsiness, tearing of the eyes, sore throat, anxiety, numbness in the limbs, and impaired swallowing and speech. It is difficult to determine triggers in children; a record of case history and subjective assessment of complaints are less informative; sometimes the symptoms may be transitory or indistinct. The article presents two clinical cases of a diagnostic search for anaphylaxis causes in young children. A diagnostic protocol includes a comprehensive study of a case history and complex determination of a patient’s sensitization profile. A boy developed anaphylaxis (skin, gastrointestinal, respiratory, neurological symptoms) after consumption of a dessert. On examination, storage proteins were detected: hazelnut (Cor a 14) and walnut (Jug r 1). A girl developed anaphylaxis (skin and respiratory symptoms) after exposure to dry fish (carp, cod), which the child was holding in her hands. On examination, parvalbumins were detected: Atlantic cod (Gad m 1), carp (Cyp c 1), Atlantic herring (Сlu h 1), Atlantic Scomber (Sco s 1), tuna (Thu a 1), and swordfish (Хір g 1). Conclusions. Based on a complex examination, patients received consistent recommendations on the peculiarities of a diet, lifestyle, as well as the need for an urgent medication — an epinephrine auto-injector. Each case of anaphylaxis requires exact identification of the cause of its occurrence, which plays a leading role in the prevention of recurring episodes and reduction of the risk of developing life-threatening symptoms in a child.